On Bodily Absence in Humanitarian Multisensory VR - Zimanyi, Eszter; Ben Ayoun, Emma (Intermédialités / Intermediality)

(untitled) (Revue intermédialités, 2019)
Humanitarian organizations, journalists, and artists are increasingly turning to virtual reality (VR) and immersive filmmaking because of its ostensibly unprecedented ability to conjure empathic feelings that lead to humanitarian action. Recent media studies scholarship attends to the possibilities and pitfalls of curating empathy through VR in the context of documentary filmmaking; however, these analyses primarily focus on VR’s unique visual address. The status of the participant’s body, as it exists in the physical world and as it is conjured within the virtual environment, remains under-explored in scholarship on immersive media and humanitarianism. In this paper, we offer a comparative analysis of embodiment in two recent multisensory VR film installations with humanitarian themes: Alejandro González Iñárritu’s Carne y Arena (2017) which stages an attempted border crossing between Mexico and the United States; and Hero (iNKStories, 2018), which places participants into an unnamed Syrian village during an air raid. Using bodily absence as a framework, we argue that agency, responsibility, and a humanitarian subjectivity are ambiguously constructed through the sensing of bodily and psychic borders within these contemporary VR installations. We conclude that humanitarian VR is better understood as a technology of encounter rather than one of empathy.